Evaluation of a training curriculum for some of the skillful abilities of young basketball players - Dr. Mustafa Asaad Munshed (Zien Journals, 2023)
The aim of the research is to evaluate the training curricula in some of the skillful abilities of the youth basketball players.As for the areas of research, it included the human area, which was represented by Maysan youth basketball players ,and the temporal area was determined for the period from (2/16/2023) to (05/15/2023), while the spatial area was in the halls of the clubs researched.
Keywords: evaluation; training curriculum; skill abilities; youth players